Challenges and Human Resource Strategies for Generation Z in the Digital Era - Permana, Ibar Adi; Sudrajat, Jajat (International Journal of Law Social Sciences and Management, 2024)
Generation Z, as a workforce that has grown up in the digital era, faces a number of challenges that require special attention from the Human Resources (HR) function. This article explores these challenges, including rapid technological change, differences in values, and Generation Z's expectations for the work environment. We also discuss the HR strategies needed to respond effectively to these challenges, which involve a deep understanding of Generation Z's preferences, the adoption of modern technology, and the upskilling of digital skills. Additionally, this article discusses the importance of strengthening morals and ethics from a religious perspective, making Gen Z responsible warriors, accompanying Gen Z in utilizing AI technology, and building a positive personal brand for Gen Z to maintain their track record as a strategy to attract and retain Generation Z. By analyzing challenges and designing appropriate strategies, this article provides insight into how organizations can effectively manage the potential of Generation Z in the face of the ever-evolving dynamics of the digital era.